Evaluating the effectiveness of barbed reposition palatopharyngoplasty compared to uvulopalatopharyngoplasty for treatment of obstructive sleep apnea - Ahmed Ahmed Kamel; Hossam Atia El Tabbakh; Hazem Raghib Dewidar; Mahmoud Sayed El Fouly (The Egyptian Journal of Otolaryngology, 2023)
Abstract Background The majority of obstructive sleep apnea cases involve the oropharynx. The hypercollapsibility of the upper airway walls (UAWs) was the cause of obstructive sleep apnea syndrome (OSAS), which most often manifested itself at the retropalatal and/or retrolingual level. Modular and adaptable barbed snore surgery (BSS) is a novel treatment for retropalatal OSA (based on the anatomy and findings of drug-induced sleep endoscopy (DISE). Objectives To compare between the outcomes of uvulopalatopharyngoplasty and the barbed reposition palatopharyngoplasty technique, and to establish if there is indeed a significant variance in post-operative results among both types of surgeries. Patients and methods This was a prospective randomized clinical trial conducted on Department of Otorhinolaryngology, Faculty of Medicine, Cairo University, and it was carried out on 50 patients (28 males and 22 females) suffering from OSAS. They were randomly distributed into two groups: group A and group B. Results There was a substantial distinction among the two groups regarding to post-operative data, comparison between values of all domains of Sleep Apnea Quality of Life Index (SAQLI) and bleeding and nasal regurgitation after surgery. There was no substantial distinction among the two groups in terms of age, sex, body mass index (BMI), smoking, hypertension, and diabetes mellitus. Conclusion Barbed reposition pharyngoplasty is superior to traditional uvulopalatopharyngoplasty in terms of results of Apnea Hypopnea Index (AHI), Epworth Sleepiness Scale (ESS), and in Sleep Apnea Quality of Life Index (SAQLI) in addition to producing less post-operative complications as well as being easy to learn.